The Microcounseling Paradigm in the Instruction of Junior High School Students in Attending Behavior - Aldridge, Ernest Edward; Ivey, Allen E. (Canadian Journal of Counselling and Psychotherapy, 2012)
The purpose of this study was to test the validity of the microcounseling paradigm in teaching a basic counseling and interpersonal skill, attending behavior, to ninth grade students. The experimental design involved training of eight students in attending skills and comparing their interviewing effectiveness with eight untrained students. Training involved video models, self observation, cue discrimination, and reinforcement of desired behavior. The experimental group demonstrated significantly increased verbal and non-verbal attending behaviors on 7 of 13 comparisons.The implications of microcounseling for the teaching of communication skills to clients is discussed.